Pengembangan E-Module Interaktif Terintegrasi Science, Environtment, Technology, Society Pada Materi Perubahan Lingkungan - Heliza Maria; Paidi Paidi (Postgraduate, University of Mataram, 2024)
Teaching materials are one of the components needed and used by teachers when teaching. With the use of appropriate teaching materials during teaching and learning activities, it will make it easier for teachers and students to achieve competencies and learning objectives. This study aims to determine the feasibility and practicality of SETS Integrated Interactive E-Module. The type of research used is research and development with research procedures using the 4D model. The research will only be carried out until the Design stage. The results showed that the SETS Integrated Interactive E-Module is feasible to use as teaching material on environmental change material with a percentage of feasibility of 80.21% by material experts and 96.25% by media experts; SETS Integrated Interactive E-Module is practical to use as teaching material on environmental change material with a percentage of practicality of 82.11% by students, and 83.33% by biology teachers. Based on the results of the feasibility and practicality tests that have been carried out, the SETS-integrated interactive e-module is feasible and practical to use.